2015
DOI: 10.1103/physrevb.92.024103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular nitrogen acceptors in ZnO nanowires induced by nitrogen plasma annealing

Abstract: X-ray absorption near-edge spectroscopy, photoluminescence, cathodoluminescence, and Raman spectroscopy have been used to investigate the chemical states of nitrogen dopants in ZnO nanowires. It is found that nitrogen exists in multiple states: N O , N Zn , and loosely bound N 2 molecule. The results establish a direct link between a donor-acceptor pair emission at 3.232 eV and the concentration of loosely bound N 2 . This work confirms that N 2 at Zn site is a potential candidate for producing a shallow accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
(64 reference statements)
4
19
0
Order By: Relevance
“…This is clearly vivid in other experiments where variation of N 2 pressure during growth or variation of sample temperature during ion implantation results in different site occupation of atomic N in ZnO. In this regard, the formation of molecular N 2 , either at V Zn or V O site, is possible and has been investigated also. The former one is reported to be a shallow acceptor, whereas the latter is a major source of compensating donor .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…This is clearly vivid in other experiments where variation of N 2 pressure during growth or variation of sample temperature during ion implantation results in different site occupation of atomic N in ZnO. In this regard, the formation of molecular N 2 , either at V Zn or V O site, is possible and has been investigated also. The former one is reported to be a shallow acceptor, whereas the latter is a major source of compensating donor .…”
Section: Introductionmentioning
confidence: 64%
“…In literature, N‐induced modifications of defects/defect complexes in ZnO have been investigated using different spectroscopic techniques . The Raman mode near 275 cm −1 is known to be due to atomic nitrogen in the vacant oxygen sites (N O ) in ZnO .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] The energy level of the N acceptor, however, can be affected by its local surrounding, 35 complexing with residual group III impurities 36 and intrinsic defects, [37][38][39] as well as formation of N-N molecules. 40,41 Moreover, it was also suggested that the proximity to the surface lowers the formation energies of the N-related acceptors and modifies their photoionization processes. [42][43][44] This may be partly responsible for the promoted p-type conductivity in nanostructured ZnO, 21,28,40,45 though the exact physical mechanism responsible for this effect, as well as the local structure of the incorporated N acceptors, remains unknown.…”
mentioning
confidence: 99%
“…40,41 Moreover, it was also suggested that the proximity to the surface lowers the formation energies of the N-related acceptors and modifies their photoionization processes. [42][43][44] This may be partly responsible for the promoted p-type conductivity in nanostructured ZnO, 21,28,40,45 though the exact physical mechanism responsible for this effect, as well as the local structure of the incorporated N acceptors, remains unknown.…”
mentioning
confidence: 99%